A guide to Stenotrophomonas maltophilia virulence capabilities, as we currently understand them - Bhaumik, Radhika; Aungkur, Nabiha Zumana; Anderson, Gregory G. (Frontiers in Cellular and Infection Microbiology, 2024)
The Gram-negative pathogen Stenotrophomonas maltophilia causes a wide range of human infections. It causes particularly serious lung infections in individuals with cystic fibrosis, leading to high mortality rates. This pathogen is resistant to most known antibiotics and harbors a plethora of virulence factors, including lytic enzymes and serine proteases, that cause acute infection in host organisms. S. maltophilia also establishes chronic infections through biofilm formation. The biofilm environment protects the bacteria from external threats and harsh conditions and is therefore vital for the long-term pathogenesis of the microbe. While studies have identified several genes that mediate S. maltophilia’s initial colonization and biofilm formation, the cascade of events initiated by these factors is poorly understood. Consequently, understanding these and other virulence factors can yield exciting new targets for novel therapeutics.